Oral and maxillofacial surgery - Kerawala, Cyrus; Newlands, Carrie (Oxford, ENK ; New York : Oxford University Press, 2010)
Trauma -- Oral cavity and oropharygeal cancer -- Surgical dermatology -- Salivary glands -- Orthognathic surgery -- Craniofacial -- Cleft lip and palate -- Aesthetic techniques -- The temporomandibular joint -- Surgical principles and oral surgery -- Oral medicine -- Eponyms in OMFS -- Other useful facts.